2016
DOI: 10.18632/oncotarget.10304
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic reappraisal identifies MGLL overexpression as an unfavorable prognosticator in primary gastrointestinal stromal tumors

Abstract: The role of deregulated cellular metabolism, particularly lipid metabolism, in gastrointestinal stromal tumors (GISTs) remains unclear. Through data mining of published transcriptomes, we examined lipid metabolism-regulating drivers differentially upregulated in high-risk cases and identified monoglyceride lipase (MGLL) as the top-ranking candidate involved in GIST progression. MGLL expression status was examined in three GIST cell lines and two independent sets of primary localized GISTs. MGLL mRNA abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…MGLL is a serine hydrolase of the AB hydrolase superfamily. Published studies demonstrated that MGLL was correlated with colorectal cancer and gastric cancer [ 32 , 33 ]. In current analyses, we identified that MGLL was correlated with survival and participated multi-pathways in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…MGLL is a serine hydrolase of the AB hydrolase superfamily. Published studies demonstrated that MGLL was correlated with colorectal cancer and gastric cancer [ 32 , 33 ]. In current analyses, we identified that MGLL was correlated with survival and participated multi-pathways in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…HSD11B1 mRNA quantification was informative in 70 cases, for which HSD11B1 immunoexpression was assessed on whole tissue sections to correlate between mRNA and protein expression. In a large independent cohort comprising 370 primary GIST samples resected prior to 2009, tissue cores (1.5 mm) in triplicate from each sample were previously assembled into tissue microarrays (TMA) [ 13 , 14 , 18 ], which were recut to perform HSD11B1 -specific fluorescent in situ hybridization (FISH) and HSD11B1 immunohistochemistry. Among these, 213 cases were previously determined for mutations in KIT , PDGFR, and v-raf murine sarcoma viral oncogene homolog B ( BRAF ) [ 13 , 14 ], while 58 cases at various risk levels were subjected to HSD11B1 sequencing in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The clinicopathological characteristics of GISTs in TMA-based analyses and HSD11B1 sequencing were tabulated in Table 1 and Supplementary Table S1 , respectively. The details of GISTs used in HSD11B1 mRNA quantification were previously described [ 14 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDL1 expression was higher in AFIP low-risk samples than in high-risk samples. PDL1 expression was also higher in samples without metastatic 37 • Several lines of observations suggest that KIT/PDGFRA mutational status also impacts on GIST natural course, with most of PDGFRA-mutated GIST showing a more favorable outcome and GIST with a structural variant in the proximal region of KIT exon 11, for example, W557_K558del, or with exon 9 KIT mutation, that is, A502_Y503dup, behaving more aggressively. 38,39 There are other biological factors that are currently used in the diagnosis of GISTs, whose prognostic role could be investigated, since only initial studies have been published at the moment.…”
Section: Biological Markersmentioning
confidence: 99%